Analysis of the Influence of Customer Satisfaction and Service Quality Towards Brand Trust at the Creative Center Injection in Kupang City - Jeksi Siokain; Roland Y. H. Silitonga (Journal of Management Studies and Development, 2026)
This study aims to analyze the influence of customer satisfaction and service quality, both simultaneously and partially, on brand trust at Injeksi Creative Center in Kupang City. This study is based on the importance of satisfaction and service quality in building customer trust in a brand, especially in the increasingly competitive creative services sector. This study uses a quantitative approach with a sample of 100 respondents who are customers of Injeksi Creative Center. Data collection was carried out through a questionnaire compiled based on research variable indicators. The data analysis technique used is multiple linear regression analysis to determine the magnitude of the influence between the independent and dependent variables. The results of the analysis show that customer satisfaction and service quality simultaneously have a significant effect on brand trust. Partially, customer satisfaction has a positive effect on brand trust, and service quality is proven to have a significant influence on customer trust in the brand. These findings confirm that increasing satisfaction and service quality are important factors in building and maintaining customer trust.